Mortars and Concrete Incorporating Palm Oil Fuel Ash and Fly Ash - Tonduba, Yvonne William; Mirza, Jahangir (Institut Teknologi Sepuluh Nopember, 2017)
Number of researchers reported that Palm Oil Fuel Ash (POFA) and Fly Ash (FA) can be used as supplementary cementing material (SCM) in concrete. Both materials have their own significant effects on the properties of concrete and have been accepted by using them for the improvement of workability and strength of concrete. However, studies showed that FA has better pozzolanic properties than POFA. Hence, properties of mortars blended with POFA (untreated and treated) as binary blend (CUP and CTP) and ternary blend that combined with FA (CUPF and CTPF) as cement replacement were investigated. Unground POFA has been used in this study. CUPF and CTPF resulted in significant improvement in the pozzolanic activity compared to CUP and CTP of mortar mix. Pozzolanic activity of ternary blend mortar achieved the specified pozzolanic activity index of 75% based on ASTM C618. Compressive strength of the C80P15F5 concrete with 15% of treated POFA + 5% of FA by weight of binder showed a slightly higher result compared to the control mix. It is suggested that the combination of POFA and FA as pozzolanic material will improves the mechanical properties of mortars and concrete.